2019
DOI: 10.1039/c9na00331b
|View full text |Cite|
|
Sign up to set email alerts
|

Water distribution at the electrified interface of deep eutectic solvents

Abstract: Preferential asymmetric electrosorption of water onto a moderately polarized electrode surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…Intriguingly they also noted that the hydrogen bond donor urea was present in all layers and also had a surface excess for both negative and positive surface potentials. Mamme et al 55 also investigated water distribution in reline, which was shown to have a surface excess with applied potential. This supports the mixed-layer hypothesis reported here, although some charge oscillation was reported.…”
Section: Normal Force Measurements Of Ethalinementioning
confidence: 99%
“…Intriguingly they also noted that the hydrogen bond donor urea was present in all layers and also had a surface excess for both negative and positive surface potentials. Mamme et al 55 also investigated water distribution in reline, which was shown to have a surface excess with applied potential. This supports the mixed-layer hypothesis reported here, although some charge oscillation was reported.…”
Section: Normal Force Measurements Of Ethalinementioning
confidence: 99%
“…25,26 This force eld was already shown to accurately describe urea based interactions, which are key during the supramolecular gelation of urea containing compounds. 7,27 Before production, an energy minimization and temperature/ pressure equilibration step was performed to ensure steric clashes or inadequate equilibration of the NPT-ensemble would not affect the production simulation. The V-rescale thermostat and Parrinello-Rahman barostat were used with the temperature set at 300 K and the pressure at 1.0 bar.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…18,19,50 Therefore, to properly compare experimental and simulated data on the polarized interface of DES, the effect of water needs to be taken into account for the simulations. 52…”
Section: Toc Graphicsmentioning
confidence: 99%